SIFAT FISIKA TANAH PERKEBUNAN KELAPA SAWIT (Elaeis guineensis Jacq.) SETELAH DIAPLIKASI TANDAN KOSONG KELAPA SAWIT DAN LIMBAH CAIR PABRIK KELAPA SAWIT - Maysarah Maysarah; Nelvia Nelvia (DINAMIKA PERTANIAN, 2018)
The research aims to examine the effect of the application of waste processing palm oil mill (Empty Fruit Bunches and Palm Oil Mill Effluent) on soil physical properties. The research was conducted at the oil palm plantation at Pelalawan and Laboratory of Soil Science, Faculty of Agriculture, the University of Riau from March to May 2016. The study was conducted experimentally using a Completely Randomized Design (CRD), which consisted of 4 treatments (EFB, POME, EFB+POME and without application as control). Each treatment was repeated 3 times. EFB and POME have been applied to the land since 2001 with intervals giving every 6 months. Soil samples were applied EFB, POME, and EFB+POME taken on Blocks B3, Blocks B7 and Blocks C17. Soil samples were taken at a depth of 0-15 cm and 15-30 cm for disturbed and undisturbed soil. Parameters measured were soil water content, bulk density, particle density, total pore space, permeability, and soil color. Each parameter of the observed data was statistically analyzed using analysis of variance followed by Duncan's New Multiple Range Test (DNMRT) at 5% level, while the soil color was descriptively analyzed. The results showed that the application of a mixture of EFB+POME increased soil moisture and bulk density decrease significantly and tended to increase the total pore space and permeability and tends to be lower particle density than controls, but it was not evident when compared EFB applications and POME alone. Applications waste processing palm oil mill affected the color of the soil where the soil is black on the application mix EFB+POME (hue: 10 YR, value/chroma: 2/1), brown on the application EFB (hue: 10 YR, value/chroma: 4/3 ), dark brown on the application of POME (hue: 10 YR, value/chroma: 3/3) and yellowish-brown in without application (hue: 10 YR, value/chroma: 5/4).